Virtual fashion experiences in virtual reality fashion show spaces - Kim, Se Jin (Frontiers in Psychology, 2023)
Introduction: Virtual reality (VR) provides a new fashion space and fashion experience. This study focuses on immersive VR and fashion shows to empirically explore the VR fashion space and fashion experience. Insights specific to fashion have not been presented in as much depth in the literature; thus, the current findings are particularly valuable and insightful. Methods: This study employed three immersive VR (IVR) fashion show stimuli and in-depth interviews according to a semi-structured questionnaire. Collected data were analyzed based on the concept of VR space and VR experience derived through literature research. Results: The VR fashion space was divided into three types and VR experiences of cognitive presence, sensible immersion, emotional immersion, and aesthetic interaction were derived accordingly. First, the physical representation of a fashion show induced a cognitive and emotional sense of presence, in which users felt as though they had moved to the same time and place as those at the fashion show. Second, participants experienced cognitive confusion owing to the differences with a priori experiences in the fashion show space (i.e., reality and imagination coexist). Third, participants transcended the limitations of physical reality while in the fashion show space of pataphysics (which was realized with human imagination), and they moved beyond the stage of confusion that is experienced while facing realistic objects to connect to creative inspiration. Discussion: The difference in the properties of VR space may be associated with distinct VR fashion experiences. The findings suggest that 1) a priori elements such as sociocultural contexts and personal experiences differ in the experiential dimension of virtual space, 2) the VR fashion show space induces a psychological experience between brand and consumer, and 3) creative inspiration and exploratory play can be greatly induced in a user if the immersive fashion space is further from the original source.